Mastery of financial accounting and market orientation: Driving competitive advantage in Indonesian SMEs - Arifin, Arifin; Misrah, Misrah; Mujahida, Sitti; Abubakar, Herminawaty (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
SMEs play a vital role in economic growth, yet sustaining competitiveness remains a challenge. This study examines the impact of market orientation and financial acumen on SME competitiveness in Indonesia, with innovation capability and resource optimization as mediators and market dynamics and financial decision-making ability as moderators. Using Structural Equation Modeling (SEM) with SmartPLS, data were collected from 500 SME owners and managers across various regions in Indonesia. The findings confirm that market orientation and financial acumen positively influence SME competitiveness, with innovation capability and resource optimization significantly mediating these effects. Additionally, market dynamics strengthen the impact of market orientation, while financial decision-making ability enhances the effect of financial acumen on competitiveness. These results emphasize the need for SMEs to integrate market-driven strategies with strong financial management practices to sustain long-term success. Practically, SME owners should invest in financial literacy, strategic decision-making, and innovation to enhance their competitive advantage. Policymakers and financial institutions should provide financial training programs, market intelligence resources, and innovation incentives to support SME growth. Future research could explore longitudinal studies and industry-specific dynamics to refine SME competitiveness strategies.